Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Produk Balsem Pala (Studi Di Desa Brongkendk Kecamatan Fakfak Papua Barat) - Lukman Kanabaraf; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstrack Fakfak Regency has MSMEs that operate in the Nutmeg Agroindustry sector. One of the products that was successfully made was Nutmeg Balm. Nutmeg balm is made from nutmeg fat and several types of herbs grown by Fakfak farmers. Fakfak Nutmeg Balm is a brand of balm produced by BUMKam (Village-Owned Enterprise) Brongkendik Village. BUMKam was founded in 2017 and only became active as an entrepreneur in October 2020. The research aims to find scientific facts related to science. Research methods have the meaning of the sequence or procedures for researchers to find answers to problems posed by researchers, so to find answers to problems posed by researchers using a qualitative approach method. The results of the research show that four indicators in measuring marketing strategy analysis in increasing sales of nutmeg balm products in MSMEs in Brongkendik village, Fakfak sub-district, such as product, price, distribution and promotion in Brongkendik village, Fakfak district. The role of BUMKam in increasing sales of nutmeg balm products in the MSMEs of Brongkendik Village, Fakfak Regency, by looking at the product dimension indicators, can be said to have not been fully implemented well because even though the quality of the nutmeg balm product is very adequate and high quality, in terms of packaging it has not yet received a patented packaging design. and still changing Keywords : BUMKam, Nutmeg Balm, Agroindustry.